A concise history of Italy - Whelpton, Eric (R. Hale, 1964)
This concisely-written history traces the development of the Italian peninsula from its earliest history, with its roots in the Etruscan civilization, to the creation of the Republic at the close of the second World War. In these pages the reader is show with remarkable skill the evolution of the Roman state from the Sabine and Latin settlements to the vast,...